Tea Plantations in the Darjeeling Hills Geo-Ecological Impact and Livelihood Implications - Tirkey, Lalit P.; Nepal, Padam (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
The geo-ecological stability of a place has an important role in contributing to the livelihood security of its people. A disturbance to the geo-ecology of a region jeopardizes the livelihood resources of the population and creates pressures for livelihood security. Human interventions in the form of destruction of forests and degradation of land significantly alter the geo-ecology of a region. Moreover, interventions with forests result in several other forms of degradations of the geo-ecology of a region. In the light of this understanding, the present study evaluates the impact of tea plantations on the geo-ecology of Darjeeling Hills, Inia and the consequent impact on the livelihood security of the people in the region.DOI: http://dx.doi.org/10.3126/hn.v10i0.7104 Hydro Nepal Vol.10 January 2012 53-59